The new religious world - Bancroft, Anne (Hodder Wayland London, 2001)
Takes a look at eight religious groups namely, the Mormons; the Rastafarians; the Unification Church ('Moonies'); Transcendental Meditation; the Baha'is; Jehovah's Witnesses; Hare Krishnas, and the Rajneeshis. This book describes their histories, beliefs and daily lives.